2013
DOI: 10.1074/mcp.m112.019786
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Triple-negative Breast Carcinomas in Combination With a Three-tier Orthogonal Technology Approach Identifies Mage-A4 as Potential Therapeutic Target in Estrogen Receptor Negative Breast Cancer

Abstract: Breast cancer is a very heterogeneous disease, encompassing several intrinsic subtypes with various morphological and molecular features, natural history and response to therapy. Currently, molecular targeted therapies are available for estrogen receptor (ER) ؊ and human epidermal growth factor receptor 2 (Her2)-positive breast tumors. However, a significant proportion of primary breast cancers are negative for ER, progesterone receptor (PgR), and Her2, comprising the triple negative breast cancer (TNBC) group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 68 publications
1
41
0
Order By: Relevance
“…Another label-based proteomics study reported that PTPN12, a tyrosine phosphatase, inhibited cellular transformation and metastasis of TNBC cells 104 . A systematic 2D gel-based proteomic study of TNBC tissue biopsies uncovered Mage-A4 105 , a family member of Mage-A, as a unique biomarker for TNBC and HER2 patients. Additionally, a label-free proteomic study identified Iroquois homeobox protein 1 (IRX1), which is involved in metanephric nephron development, as a potential plasma biomarker for TNBC 106 .…”
Section: Triple-negative Breast Cancer (Tnbc)mentioning
confidence: 99%
“…Another label-based proteomics study reported that PTPN12, a tyrosine phosphatase, inhibited cellular transformation and metastasis of TNBC cells 104 . A systematic 2D gel-based proteomic study of TNBC tissue biopsies uncovered Mage-A4 105 , a family member of Mage-A, as a unique biomarker for TNBC and HER2 patients. Additionally, a label-free proteomic study identified Iroquois homeobox protein 1 (IRX1), which is involved in metanephric nephron development, as a potential plasma biomarker for TNBC 106 .…”
Section: Triple-negative Breast Cancer (Tnbc)mentioning
confidence: 99%
“…[2] Women with TNBC have a poor prognosis due to the aggressive nature and lack of suitable targeted therapies. [3] Presently, research progression for TNBC has not yet been studied. Thus, it is necessary to monitor the global TNBC research.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, several studies have discovered a few breast cancer associated tissue markers, such as estrogen and progesterone receptors, HER2/neu (erbB2), p53, Ki-67/MIB-1 and vascular endothelial growth factor (VEGF) [6,7]. In addition, Mage-A4 was identified as potential therapeutic target in TNBC [8].…”
Section: Introductionmentioning
confidence: 99%